A Continuing Education Activity Durably Addressed Knowledge Gaps Related to Penicillin Allergies Among Pharmacists and Pharmacy Technicians. (February 2022) - Covington, Elizabeth W.; Durham, Spencer H.; Bland, Christopher M.; Bookstaver, P. Brandon; Chahine, Elias B.; Cho, Jonathan C.; Diggs, Fernando; Jones, Bruce M.; Kyle, Jeffrey A.; Stover, Kayla R.; Wagner, Jamie L.; Hughes, Peter J.
Background: Penicillin allergy is one of the most frequent self-reported allergies; however, only about 10% of reported allergies are accurate.Objectives: Through the creation of a continuing pharmacy education (CPE) activity, we sought to assess knowledge gaps and comfort levels in the management of penicillin allergies.Methods: A 1-hour enduring-content CPE activity was offered as an interactive course from September 20, 2019, to September 20, 2020. Participants completed 3 surveys (pre-survey, post-survey, and follow-up survey). Participants were pharmacists and pharmacy technicians who completed, at a minimum, the activity and both pre- and post-surveys. The primary outcome was the percentage of participants scoring >80% on knowledge-based questions on the post-survey compared with the pre-survey. Secondary outcomes included pre-post comparisons on knowledge-based questions, participants' self-report of an allergy, and comfort levels dispensing cephalosporins in a patient with a self-reported penicillin allergy.Results: A total of 389 participants completed the CPE activity, with 176 included for analysis. Significantly more participants scored >80% on knowledge-based questions on the post-survey compared with the pre-survey (71.6% vs 22.7%, P < .001). There was no significant difference between the percentage of participants scoring >80% on the post-survey and the follow-up survey (71.6% vs 65%, P = .119). The majority of participants (74%) felt comfortable dispensing a cephalosporin in a patient with a penicillin allergy on the pre-survey, with similar percentages on the post- and follow-up surveys (77% and 90%, respectively).Conclusion: A targeted continuing education program improved overall knowledge, which was sustained for up to 2 months.